Glucose monitoring using implanted fluorescent microspheres. - McShane, M.J (IEEE Engineering in medicine and biology magazine)
The authors are working toward a minimally invasive means for diabetics to better monitor glucose levels. A fiber-optic probe was fabricated for delivery and collection of light to an implanted sensor. The probe and associated optical system has high sensitivity and allows for flexible, remote measurements. The system was used to collect data with sensor solutions similar to what is envisioned for the implantable system, and the recorded spectra were processed in an attempt to predict glucose concentrations from fluorescence measurements. Despite the availability of sophisticated multivariate calibration methods, the best prediction results were obtained using polynomial regression with regression coefficient ratios. The measurements are far from perfect, but they do meet the requirements for clinical use and show promise for further improvement in the future. In vivo experiments were conducted using "simulated" sensors that had constant fluorescence characteristics. Results of implantation in excised skin and in live animals indicate that, while very strong fluorescence signals were measured for implanted particles, the current sensor chemistry must be improved for adequate resolution. In addition, difficulty in achieving repeatable injection depths and homogeneity of mixtures containing different colored spheres confounded attempts to make true quantitative measurements.